Assessing Benefit Portability for International Migrant Workers : A Review of the Belgium-Morocco Bilateral Social Security Agreement - Holzmann, Robert (World Bank, Washington, DC, 2016)
The portability of social benefits is gaining importance given the increasing share of individuals working at least part of their life outside their home country. Bilateral social security agreements (BSSAs) are considered a crucial approach to establishing portability, but the functionality and effectiveness of these agreements have not yet been investigated; thus, important guidance for policy makers in migrant-sending and migrant-receiving countries is missing. To shed light on how BSSAs work in practice, this document is part of a series providing information and lessons from studies of portability in four diverse but comparable migration corridors: Austria-Turkey, Germany-Turkey, Belgium-Morocco, and France-Morocco. A summary policy paper draws broader conclusions and offers overarching policy recommendations. This report looks specifically into the working of the Belgium-Morocco corridor. Findings suggest that the BSSA is broadly working well, with no main substantive issues in the area of pension portability, except for the non-portability of the noncontributory top-up pension and issues with widows’ pensions in case of divorce and repudiation, and in health care, the pending introduction of portable health care for retirees with single pensions from the other country. Process issues around information provision in Morocco and automation of information exchange are recognized.